ATF2 predicts poor prognosis and promotes malignant phenotypes in renal cell carcinoma. Issue 1 (December 2016) - Wu, Deng-shuang; Chen, Cheng; Wu, Zhen-jie; Liu, Bing; Gao, Li; Yang, Qing; Chen, Wei; Chen, Jun-ming; Bao, Yi; Qu, Le; Wang, Lin-hui
Abstract Background Activating transcription factor 2 (ATF2) is a basic helix-loop-helix transcription factor, which has been shown to participate in the pathobiology of numerous cancers. However, the role of ATF2 in renal cell carcinoma (RCC) remains unclear. Methods ATF2 knockdown and overexpression studies were performed in RCC cells to evaluate changes in cell viability, cell cycle, apoptosis, migration and invasion. Xenograft models were used to examine the tumorigenic and metastatic capability of RCC cells upon ATF2 suppression. The expression of ATF2 in human RCC samples was determined using immunohistochemistry on a tissue microarray. Results ATF2 knockdown in RCC cells reduced their proliferative and metastatic potentials, whereas ATF2 overexpression enhanced these properties. Mechanistic studies revealed that the transcription of CyclinB1, CyclinD1, Snail and Vimentin was directly regulated by ATF2 in RCC cells. Moreover, ATF2 was shown to be highly expressed in RCC tissues, especially in tumors with metastases. High expression of ATF2 correlated with aggressive clinico-pathological characteristics and predicted poor prognosis of RCC patients. Conclusions ATF2 exerts an oncogenic role in RCC and could serve as an important prognostic biomarker.